Friday

April 18, 2014

April 18, 2014

Posted by **Brandon** on Thursday, May 12, 2011 at 6:21pm.

1. P(x)=x^4+4x^3-16x-16; r=-2

2. P(x)=x^5+3x^4+2x^3-2x^2-3x-1; r=-1

3. When x^3-5x^2+4x+5 is divided by x-c, the quotient is x^2-3x-2 and the remainder is 1. Find c.

Thanks

- Algebra 2 -
**Mgraph**, Thursday, May 12, 2011 at 7:41pm1. P(x)=(x-2)(x+2)^3 3 times

2. P(x)=(x-1)(x+1)^4 4 times

3. x^3-5x^2+4x+5=(x^2-3x-2)(x-c)+1=>5=2c+1

c=2

**Related Questions**

bobpursley,math - about this problem , I figured it out and i did get the answer...

algebra - simplify (6x^3-16x^2+11x-5)/(3x-2) (3x-2)(2x-1)^2-3 my muliple choice ...

Math - Can someone please check my answers below for accurateness? The ...

Pre-algebra - I have some practice problems, and I need to have them worked out...

Pre-algebra - I have some practice problems, and I need to have them worked out...

math,bobpursly, - 4x-2x^2+4x^3 from 4x^3+x-3x^2 4x^3+x-3x^2 -( 4x-2x^2+4x^3) ...

Math - Can you check these questions for me? 1. Add: (3x^4-x+2)+(9x^5-x^2+x) 9x^...

Math - Use synthetic division to find the quotient and remainder: (2x^5-7x^3-5x...

Intermediate Algebra - Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^...

algebra - 1)Write the expression 9n^6+7n^3-6 in quadratic form,if possible A.9(n...